Optimalisasi Layanan Kesehatan Lansia, Ibu dan Anak Melalui Kegiatan Kuliah Kerja Nyata (KKN) di Posyandu Kelurahan Lubang Panjang, Kecamata Barangin, Kota Sawahlunto - wilda welis; Haliyahtul H; Dynda Imela; Puti Shahira N; Lingga Fajar A; Yolandari (Jurnal IKEOR, 2025)
The Community Service Program (KKN) is a concrete form of student community service, particularly in efforts to improve the quality of health services at the primary level. This article discusses the optimization of health services for the elderly, mothers, and children through KKN activities carried out at the Integrated Health Post (Posyandu) in Lubang Panjang Village, Barangin District, Sawahlunto City. This activity aims to support the improvement of preventive and promotive health services through cadre mentoring, health education, and technical assistance in implementing Posyandu activities. The methods used include field observation, coordination with health workers and Posyandu cadres, implementation of nutrition and health counseling, and direct involvement in weighing activities, height measurements, and recording community health data. The results of the activity show an increase in community participation, especially the elderly and mothers of toddlers, in Posyandu activities, as well as increased awareness of the importance of routine health checks. This activity also strengthens the synergy between students, Posyandu cadres, and the community in creating an environment that supports shared health. Thus, KKN activities